2019
DOI: 10.31234/osf.io/r6njf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Greater visual working memory capacity for visually-matched stimuli when they are recognized as meaningful

Abstract: Almost all models of visual working memory assume it has a fixed capacity: some models propose a limit of 3-4 objects, where others propose there is a fixed pool of resources for each basic visual feature. Recent findings, however, suggest that memory performance is improved for real-world objects. What supports these increases in capacity? Here, we test whether the meaningfulness of a stimulus alone influences working memory capacity while controlling for visual complexity and directly assessing the active co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 32 publications
5
21
0
Order By: Relevance
“…Overall, in a series of high-powered, preregistered experiments, we find that (1) foils chosen to be dissimilar by VGG16 are, in fact, particularly dissimilar according to human participants; (2) this dissimilarity modulates memory performance, such that participants perform better at memory tasks with such dissimilar foils than the randomly-chosen cross-category foils sometimes used in previous work, and (3) when we use equivalently chosen, maximally dissimilar foils for both colors and objects, we find a large benefit for objects relative to colors at long encoding times, replicating previous results of higher working memory capacity for meaningful objects (Brady et al, 2016;Asp et al, 2019). Consistent with this as an explanation for previous failures to find such advantages, we also find such effects are reduced when comparing maximally distinct color foils vs. randomly-chosen, nonmaximal object foils, indicating that the lack of behavioral object benefits in some previous studies (Quirk et al, 2020;Li et al, 2020) were indeed due to their making an unfair comparison between different kinds of stimuli.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, in a series of high-powered, preregistered experiments, we find that (1) foils chosen to be dissimilar by VGG16 are, in fact, particularly dissimilar according to human participants; (2) this dissimilarity modulates memory performance, such that participants perform better at memory tasks with such dissimilar foils than the randomly-chosen cross-category foils sometimes used in previous work, and (3) when we use equivalently chosen, maximally dissimilar foils for both colors and objects, we find a large benefit for objects relative to colors at long encoding times, replicating previous results of higher working memory capacity for meaningful objects (Brady et al, 2016;Asp et al, 2019). Consistent with this as an explanation for previous failures to find such advantages, we also find such effects are reduced when comparing maximally distinct color foils vs. randomly-chosen, nonmaximal object foils, indicating that the lack of behavioral object benefits in some previous studies (Quirk et al, 2020;Li et al, 2020) were indeed due to their making an unfair comparison between different kinds of stimuli.…”
Section: Introductionsupporting
confidence: 83%
“…In the current work, and in our previous work, we aim to achieve a level of deep processing, focused on individual items, by using long encoding times (e.g., Brady et al, 2016;Asp et al, 2019). However, in other recent work we have shown that while this does result in a benefit of objects relative to colors, this is far from the most effective manipulation in promoting a focused one-item-at-once encoding strategy, and a more effective manipulation is to actually show objects sequentially at encoding (one at a time; .…”
Section: Other Differences That May Be Relevant For Colors Vs Objectmentioning
confidence: 99%
“…Across multiple experiments, they found that Chinese participants were better in detecting changes in the characters' shape but not in other aspects of these characters, such as their color or font type. These results provide novel evidence for an influence of LTM on VWM performance within the domain of word forms, contributing to a growing literature investigating the effects of familiarity and expertise on VWM performance (Jackson and Raymond, 2008 ; Curby et al, 2009 ; Kaiser et al, 2015 ; Xie and Zhang, 2017 ; Asp et al, 2019 ).…”
supporting
confidence: 55%
“…For example, real-world objects, compared to simple stimuli, allow access to significant additional information (for example, the real size of the objects: Konkle have specific expertise with certain object categories (Curby & Gauthier, 2007;Curby, Glazek, & Gauthier, 2009;Janini & Konkle, 2019;Xie & Zhang, 2017), all of which may be used to enhance working memory. In fact, several studies have shown that the capacity of visual working memory for real-world objects differs from that of simple stimuli, in particular being less fixed and more dependent on the particular stimuli used and how much meaningful information about them can be processed (Asp, Störmer & Brady, 2019;Brady, Störmer, & Alvarez, 2016). For example, Brady and colleagues (2016) showed a boost in performance for real-world objects that was attributable to more active storage in visual working memory, consistent with a theory where additional high-level information about such objects, perhaps in the ventral stream, is maintained in working memory in addition to low-level information.…”
mentioning
confidence: 99%